Ekplorasi Etnomatematika Ulos Tikar pada Materi Himpunan - Darma Indra Gultom; Remia Warni; Hizkia Ronaldus Silalahi; Riko Kurniawan; Maria Isadora; Agusmanto JB Hutauruk; Simon M Panjaitan (Jurnal Pendidikan Matematika:Judika Education, 2022)
The purpose of this study was to explore and find the set material on ulos mats made by ulos craftsmen in Pematangsiantar city which are mostly found as home industries. The research method used in this research is descriptive qualitative with an ethnographic approach. Data obtained by domain analysis and taxonomic analysis. The results of the study obtained the terms Kasuksak, flies, binoculars, weft thread, throwing thread, wool thread, lotak, Ulos Mats which can be used in mathematics lessons on set material. In conclusion, the exploration of ulos mats provides a fun, new nuanced mathematics learning experience, which students can find in everyday life and invites students to get to know the culture around them. Keywords: Yarn, Sets, Mathematics, Ulos mats